2006
DOI: 10.1007/s10654-005-5699-8
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Food and Nutrient Index and All Cause Mortality

Abstract: Although it is not demonstrated in our study, we think that the overall approach offers an opportunity to improve our understanding of the role of diet in the risks of morbidity or mortality associated with the overall dietary pattern rather than some individual foods and nutrients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Both approaches provided similar findings when the pattern was tested against morbidity and/or mortality, with benefits bound to characteristics defined as ‘Mediterranean diets’ or to the prevalence of plant foods over animal foods. Similar findings were identified in population samples of different countries, such as Belgium ( 13 ) , Canada ( 28 ) , Costa Rica ( 21 ) , Denmark ( 8 ) , Great Britain ( 23 , 27 ) , Greece ( 3 , 9 , 24 , 26 ) , Italy ( 4 , 10 , 18 , 31 ) , Japan ( 20 ) , the Netherlands ( 16 ) , Spain ( 29 , 30 ) , Sweden ( 15 ) and the USA ( 17 , 22 ) , and pooling or comparing different countries ( 5 – 7 , 11 , 14 , 19 , 25 ) . This suggests that some dietary characteristics may have protective effects in rather different populations and cultures and be related to CHD, CVD and all-cause mortality.…”
Section: Discussionsupporting
confidence: 85%
“…Both approaches provided similar findings when the pattern was tested against morbidity and/or mortality, with benefits bound to characteristics defined as ‘Mediterranean diets’ or to the prevalence of plant foods over animal foods. Similar findings were identified in population samples of different countries, such as Belgium ( 13 ) , Canada ( 28 ) , Costa Rica ( 21 ) , Denmark ( 8 ) , Great Britain ( 23 , 27 ) , Greece ( 3 , 9 , 24 , 26 ) , Italy ( 4 , 10 , 18 , 31 ) , Japan ( 20 ) , the Netherlands ( 16 ) , Spain ( 29 , 30 ) , Sweden ( 15 ) and the USA ( 17 , 22 ) , and pooling or comparing different countries ( 5 – 7 , 11 , 14 , 19 , 25 ) . This suggests that some dietary characteristics may have protective effects in rather different populations and cultures and be related to CHD, CVD and all-cause mortality.…”
Section: Discussionsupporting
confidence: 85%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] In China, the Chinese Food Pagoda score assesses the adherence to the Chinese Food Pagoda, which is based on food groups according to the Dietary Guidelines for Chinese. 19 The concept of the Chinese Food Pagoda score is similar to that of the Japanese Food Guide Spinning Top.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…10 Higher diet quality scores have been consistently associated with a lower risk of mortality. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] All cause mortality was reportedly reduced by 11-42%, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] cardiovascular disease mortality by 17-60%, 10 11 14-16 18-20 22-24 and cancer mortality by 11-40% 11 14-16 18 19 23 in individuals with the highest category of scores of diet quality compared with individuals with the lowest category. To the best of our knowledge, only two Asian studies have previously examined the association between diet quality and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified dietary factors associated with mortality. Those found to correlate with reduced mortality include nuts, 14 fruit, 5,6 cereal fiber, 2 polyunsaturated fatty acids (PUFAs), 2 ω-3PUFAs, 3 green salad, 7 Mediterranean dietary patterns, 811 “healthy” or “prudent” dietary patterns, 10,12,13 plant-based diet scores, 14 plant-based low-carbohydrate diets, 15 and vegetarian diets. 4,16,17 Associations with increased mortality have been found for a high glycemic load, 2 meat, 6,7 red meat, 18,19 processed meat, 18,19 eggs, 7 potatoes, 5 increased energy intake, 20 and animal-based low-carbohydrate diets.…”
mentioning
confidence: 99%